2005
DOI: 10.1007/s00701-004-0458-2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal subarachnoid hematomas: our experience and literature review

Abstract: MRI and CT are not usually diagnostic because they are not able to differentiate between a subarachnoid lesion and a subdural one. However, diagnosis may be possible when these investigations detect the CSF or the contrast medium surrounding the hematoma. Although the risks of producing spinal subarachnoid hematoma as a result of LP are remote, this is, in fact, the primary cause in patients with coagulopathies. The results of treatment depend on the patient's initial neurological condition, the severity of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 42 publications
1
129
0
2
Order By: Relevance
“…Although earlier studies reported that lumbar SDH arose after direct trauma to the hip or lumbar region, 6,19 we suspected migration from the intracranial to the lum bar area. To identify the rate of coincidental SDH and to remove the bias of their attribution to trauma to the hip or lumbar region, we compared their rate in patients who had sustained head trauma only with the rate in patients with multiple traumas.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Although earlier studies reported that lumbar SDH arose after direct trauma to the hip or lumbar region, 6,19 we suspected migration from the intracranial to the lum bar area. To identify the rate of coincidental SDH and to remove the bias of their attribution to trauma to the hip or lumbar region, we compared their rate in patients who had sustained head trauma only with the rate in patients with multiple traumas.…”
Section: Resultsmentioning
confidence: 66%
“…Its pathogenesis has been considered secondary to coagulopathies (including SDH arising after anticoagulant therapy), lumbar punc ture, vascular malformations, traumatic injuries, low CSF pressure, and idiopathic causes, factors that may be pres ent singly or in various combinations. 6,15,19 No etiologic factor for bleeding was identified in 17.3%-29.7% of these patients, and most spinal SDHs were observed in patients with vascular malformations and in patients treated by anticoagulant therapy, although this therapy alone is not thought to elicit spinal hemorrhage. 6,19 Diagnostic MRI studies show the size and extent of the hemorrhage and its relationship to the spinal cord.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations